2018
DOI: 10.1007/s12539-018-0289-0
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Mechanisms of Active Compounds in Traditional Chinese Medicine for the Treatment of Influenza Virus by Virtual Screening

Abstract: In recent years, new strains of influenza virus such as H7N9, H10N8, H5N6 and H5N8 had continued to emerge. There was an urgent need for discovery of new anti-influenza virus drugs as well as accurate and efficient large-scale inhibitor screening methods. In this study, we focused on six influenza virus proteins that could be anti-influenza drug targets, including neuraminidase (NA), hemagglutinin (HA), matrix protein 1 (M1), M2 proton channel (M2), nucleoprotein (NP) and non-structural protein 1 (NS1). Struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…3B ). In general, docking scores with binding energy ≤−5.0 kcal/mol indicate good compound-target interaction 33 , 34 . The binding energy between kaempferol and PPARG, PTGS2, F2, TNF were −7.94, −7.80, −8.80, −6.84 kcal/mol, respectively, indicating that kaempferol could interact with PPARG, PTGS2, F2, and TNF.…”
Section: Resultsmentioning
confidence: 99%
“…3B ). In general, docking scores with binding energy ≤−5.0 kcal/mol indicate good compound-target interaction 33 , 34 . The binding energy between kaempferol and PPARG, PTGS2, F2, TNF were −7.94, −7.80, −8.80, −6.84 kcal/mol, respectively, indicating that kaempferol could interact with PPARG, PTGS2, F2, and TNF.…”
Section: Resultsmentioning
confidence: 99%
“…In the search for new antiviral drugs, studies have been conducted on molecular docking and molecular dynamics simulations to identify components or derivatives of Chinese medicines or TCM formulations that can block channel activity or drugs at sialic acid binding sites. A study examined six viral proteins that could be targeted by antiviral drugs, including neuraminidase, Hemagglutinin, matrix protein 1, M2 proton channel, nucleoprotein, and nonstructural protein 1 [ 82 ]. Molecular docking techniques were used to identify potential inhibitors of 13,144 TCM compounds.…”
Section: Discussionmentioning
confidence: 99%
“…The interactions of these compounds with host targets were studied by molecular reverse docking. Finally, it was found that 22 compounds inhibitors could stably bind to host targets with high binding free energy [ 82 ].…”
Section: Discussionmentioning
confidence: 99%
“…Traditional Chinese medications have been proved to play a critical role in the prevention and treatment of several virus diseases, such as in uenza virus, herpes simplex virus type 1 (HSV-1), SARS, and hepatitis B virus [29][30][31]. In clinical practices, traditional Chinese medications participated in patients' treatment collectively and were employed according to syndrome differentiation and stage of disease.…”
Section: Discussionmentioning
confidence: 99%